Ultrasonic Investigation of Molecular Interactions in Binary Mixtures at 303 K - R. Nithya; S. Nithiyanantham; S. Mullainathan; M. Rajasekaran (E-Journal of Chemistry)
The ultrasonic velocity, density and viscosity at 303 K have been measured in the binary systems of toluene with benzene and o-xylone with benzene. The acoustical parameters such as adiabatic compressibility, free length, free volume and acoustical impedance are calculated. The results are interpreted in terms of molecular interaction between the components of the mixtures